The Semi-Aquatic Freshwater Earthworm Genus Glyphidrilus Horst, 1889 from Myanmar (Oligochaeta: Almidae) with Description of a New Species - Chanabun, Ratmanee; Lin, Aung; Jirapatrasilp, Parin; Bantaowong, Ueangfa (Tropical Natural History, 2020)
After the publication of the comprehensive monograph on Burmese earthworms by Gordon E. Gates in 1972, there has only been one recent publication by Csuzdi et al. (2015), which reported seven species records belonging to the families Moniligastridae, Benhamiidae, Octochaetidae and Megascolecidae, but did not include any species in the family Almidae. During 2015–2016, we collected Glyphidrilus samples (family Almidae) from some parts of Myanmar under the Fauna and Flora International (FFI) program, resulting in the discovery of Glyphidrilus tonywhitteni Chanabun and Panha, new species. It differs from its congeners by having clitellar wings at 21–25, ½26, clitellum location at 14, 15–30, 31, genital markings paired on bc at 13, 14–20 and 26 and on aa at 11–13, 14, and spermathecae at 13/14–15/16.